Overview of the CHILL-ICE 2021 Science Experiments and Research Campaign - David J. K. Smith; Charlotte R. Pouwels; Marc Heemskerk; Benedetta M. Cattani; Esther Konijnenberg; Robert Heemskerk; Sebasthian Ogalde (Space: Science & Technology, 2022)
The main objective of the CHILL-ICE (Construction of a Habitat Inside a Lunar-analogue Lava tube—Iceland; a campaign by ICEE Space and EuroMoonMars) prototype mission was to deploy an inflatable habitat and its systems inside a lunar analogue lava tube. This took place during an 8-hour extra vehicular activity (EVA) with three analogue astronauts as part of a three-day mission. CHILL-ICE 2021 was carried out in July/August 2021 and consisted of two missions and was accomplished through successful collaboration of nonprofit research organizations, agencies, companies, and universities across 16 nations. The pilot campaign successfully reached its main objective: the testing of emergency equipment designed to help astronauts survive when first arriving to a new celestial body and to perform experiments similar to those that would be carried out off-planet. This article is a review of the scientific research experiments carried out during and after the mission: SpotNet, an artificial intelligence (AI) astronaut detection vision system; training for studies of the geological surroundings examined during EVAs; astronaut vigilance experiments carried out before, during, and after the mission; and Lunar Zebro, a legged rover intended to assist the crew in traversing and exploring harsh terrain.